Corrosion inhibition of mild steel in hydrochloric acid solution using fatty acid derivatives - Mohd, Noor Khairin; Ghazali, Mariyam Jameelah; Yeong, Shoot Kian; Ibrahim, Nor Azowa; Wan Yunus, Wan Md. Zin; Mohd Noor, Siti Mariam; Idris, Zainab (Malaysian Palm Oil Board, 2017)
The inhibitive actions of fatty acid derivatives namely palmitate hydrazide (PH), N-ethylidene palmitate hydrazide (EPH) and N-phenylmethylidene palmitate hydrazide (PPH) on mild steel in 1 M hydrochloric acid were investigated using open circuit potential, linear polarisation and electrochemical impedance spectroscopy techniques. It was observed that the percentage of inhibition efficiency (η%) increased with increasing concentrations of inhibitor and temperature of test medium. The maximum η% approaches 85% in the presence of 200 mg litre-1 of inhibitors EPH and PPH at 308 ± 1K. The inhibitor efficiencies were found to be in the following order: PPH>EPH>PH. The adsorption of these inhibitors on mild steel surface obeys Langmuir adsorption isotherm. They act as mixed-type inhibitors. Scanning electron microscopy-energy dispersive X-ray (SEM-EDX) was also carried out on polished mild steel coupons and those immersed in the test medium with the absence and presence of 200 mg litre-1 of the inhibitors studied.